Comparing the effectiveness of schema therapy and therapy based on emotional efficiency on rumination and emotional expression of divorced women in Tehran - Ghadiani, Maryam; Nejad Hosseini, Saeideh (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The purpose of this research is to compare the effectiveness of schema therapy and therapy based on emotional efficiency on rumination and emotional expression of divorced women in Tehran. Method: The research design was experimental studies with a semi-experimental design and a pre-test-post-test type with a control group. The current research population includes all divorced women in the 5th district of Tehran, of which 45 people were selected as the sample size by cluster sampling method, and were randomly divided into three experimental and control groups of 15 people. Both groups answered the rumination scale of Nalan Hoeksma and Maro (1991) and the emotion expression scale of King and Ammons et al. (1990) in two phases: pre-test, post-test and follow-up. The first experimental group received schema therapy based on Yang et al.'s (2003) protocol, and the second experimental group received emotional efficiency therapy based on McKay and West's (2016) protocol for ten sessions, and two 90-minute workshop sessions per week. Received, but the control group did not receive training. The data were analyzed by variance analysis with repeated measurements and Spss.22 software. Results: The results showed that schema therapy and therapy based on emotional efficiency was effective on rumination (F=8.00, P=0.009) and emotional expression (F=6.68, P=0.016) of divorced women. Also, the results showed that schema therapy had a greater effect on women's rumination and emotional expression compared to treatment based on emotional efficiency. Conclusion: It is possible to use both schema therapy and therapy based on emotional efficiency to improve the psychological problems of divorced women.